FACTOR ANALYSIS THAT EFFECT UNIVERSITY STUDENT PERCEPTION IN UNTIRTA ABOUT EXISTENCE OF REGION REGULATION IN SERANG CITY - Hadi Suprapto Arifin; Ikhsan Fuady; Engkus Kuswarno (BPSDMP Kominfo Manado, 2017)
This research's purposes are for; (a). To know the influence of internal factors at university student perception about the existence of syari'ah region regulation in serang city (b). To know the influence of exteenal factors at university student perception about the existence of syari'ah region regulation in serang city. This research is designed with positivistic paradigm with survey rapproachement, this research population is all of active university student in Sultan Agung Tirtayasa University. The data anlysis in this research uses doubled linear regretion analysis. The analysis result is known generally as individual internal factors and individual external factors have a real effect to university student perception about the existence of syari'ah region regulation. Internal factors that effect the university student perception about the existence of region regulation are cosmopolitan variable, assessment to syari'ah region regulation, and region regulation exeistence expectation. Internal variable has positive effect and significant to perception. Exeternal factors that effect university student perception about the existence of region regulation are syari'ah region regulation characteristic variable and environment characteristic. This external variable has an positive effect and significant to perception. Keywords : perception, policy, syari'ah region regulation. Penelitian ini bertujuan untuk; (a). Untuk mengetahui pengaruh faktor faktor internal terhadap persepsi mahasiswa tentang keberadaan perda syariah di Kota Serang (b). Untuk mengetahui pengaruh faktor faktor eksternal terhadap persepsi mahasiswa tentang keberadaan perda syariah di Kota Serang. Penelitian ini di desain dengan paradigma positivistik dengan pendekatan survey, populasi penelitian ini adalah semua mahasiswa aktif di Universitas Sultan agung Tirtayasa. Analisis data pada penelitian ini dengan menggunakan analisis regresi linier berganda. Hasil analisis diketahui secara umum faktor faktor internal dan ekternal individu memiliki pengaruh yang nyata terhadap persepsi mahsiswa akan keberdaaan perda syariah. faktor Internal yang mempengaruhi persepsi mahasiswa terhadap keberadaan perda antara lain variabel kosmopolitan, penilaian terhadap perda syariah, serta harapan/ekspektasi keberadaan perda. Variabel internal memiliki pengaruh positif dan signifikan terhadap persepsi. Faktor eksternal yang mempengaruhi persepsi mahasiswa terhadap keberdaan perda antara lain variabel karakteristik Perda syariah dan karakteristik Lingkungan. Variabel eksternal ini memiliki pengaruh positif dan signifikan terhadap persepsi. Kata kunci: persepsi, kebijakan, perda syariah